The Role of Notaries in Efforts to Settle Disputes Over the Distribution of Inheritance Property in Batang Regency - Adiyanto, Hanif; Riyanto, Taufan Fajar; Bawono, Bambang Tri (Jurnal Konstatering, 2025)
Abstract. This study aims to determine and analyze the Implementation of the Role of Notaries in Efforts to Resolve Disputes over the Distribution of Inheritance in Batang Regency and to determine and analyze the Effectiveness of the Implementation of the Settlement of the Distribution of Inheritance in Front of a Notary in Batang Regency. The approach method in this study is a sociological juridical approach. Types and Sources of data use primary data, secondary data and tertiary data. Data collection uses primary data and secondary data. The data analysis method used is prescriptive analysis. The results of the research and discussion in this study are: 1) The implementation of the role of notaries in efforts to resolve disputes over the distribution of inheritance in Batang Regency has a significant contribution, especially in terms of making authentic deeds that serve as a strong legal basis to avoid future conflicts. Notaries act as neutral parties who provide legal consultation services, ensure clarity of the rights and obligations of the heirs, and assist in the effective mediation process so as to accelerate the peaceful resolution of disputes. However, there are still obstacles in the form of a lack of public understanding of the importance of notary involvement in the inheritance distribution process, as well as limited access for some communities in remote areas. 2) The implementation of the settlement of inheritance distribution before a Notary in Batang Regency shows varying effectiveness depending on several factors such as the level of public understanding of inheritance law (both Islamic law and civil law), the participation of dispute resolution institutions such as Religious Courts and traditional leaders, as well as legal awareness and the will to peace from the heirs. In practice, there are still significant obstacles, such as the lack of valid supporting documents, inconsistencies in heir data, and the existence of prolonged internal family conflicts. However, on the other hand, mediation efforts, both informally facilitated by community leaders and formally through judicial institutions, have shown a positive contribution in accelerating the resolution of inheritance disputes.